Toda Solitons: Properties and Applications III Data Transmission - Chai, Rong (My University, 2007)
Solitons are solutions to a special class of nonlinear partial differential equations representing certain nonlinear systems. Solitons possess some very interesting transmission properties through nonlinear systems. In this thesis, we examine the properties of Toda solitons and Toda circuits. The time-frequency characteristics, time-bandwidth product, and energy of the single and composite solitons are studied. The response of the Toda circuit to both deterministic and stochastic inputs are analysed and examined via Volterra series and Runge-Kutta method. The application of the Toda solitons as a message carrier in a data communication system is then proposed. Both single user transmission and a multiplexing scheme exemplified by a two-user transmission scenario are considered. The bandwidth efficiency of the soliton communication system is studied and compared with other systems. The detection performance of the soliton communication system is studied and compared with traditional signalling schemes. Theoretical analysis and numerical results demonstrate that soliton system offers high bandwidth efficiency and high robustness against channel noise for amplitude detection due to the special properties of the soliton and the Toda circuit. The response of mismatched Toda circuit to input soliton is studied and the detection performance of soliton system with mismatched Toda circuit is also examined. It is shown that the slightly mismatched Toda circuit may not affect the detection performance of soliton system, while the mismatched Toda circuit with large mismatch coefficient may deteriorate the system performance seriously.
Keywords: toda solitons; application data transmission; Electrical and Computer Engineering; Electrical and Computer Engineering